Explaining Compassion Organizing - Dutton, Jane E.; Worline, Monica C.; Frost, Peter J.; Lilius, Jacoba (Administrative Science Quarterly, 2006)
We develop a theory to explain how individual compassion in response to human pain in organizations becomes socially coordinated through a process we call compassion organizing. The theory specifies five mechanisms, including contextual enabling of attention, emotion, and trust, agents improvising structures, and symbolic enrichment, that show how the social architecture of an organization interacts with agency and emergent features to affect the extraction, generation, coordination, and calibration of resources. In doing so, our theory of compassion organizing suggests that the same structures designed for the normal work of organizations can be redirected to a new purpose to respond to members' pain. We discuss the implications of the theory for compassion organizing and for collective organizing more generally.